My big story bible - Wright, N. T. (SPCK, 2024)
" My Big Story Bible not only offers a faithful and vibrant retelling of all the major Bible stories of the Old and New Testament, but theologian Tom Wright invites children to discover the many surprising ways in which the stories link to one another, and how together they form the BIG STORY of God's plan to make everything right and bring heaven and earth together when Jesus returns. Tom Wright highlights both familiar characters and events, but also key passages from other parts of Scripture which often go missing in other Children's Bibles - the Psalms, Proverbs, the Prophets and the letters of Paul - all of which help to explain the BIG STORY that God wants all people to hear."--Publisher